Evaluation of the Nutritional and Biochemical Variation in Pistachios Exposed to Dielectric Barrier Discharge Plasma - Mahdiyeh Bakhtiyari-Ramezani; Fatemeh Amani; Aboutorab Naeimabadi (Future Foods)
Cold plasma processing systems have proven to be promising tools for reducing biological and chemical contaminants in the food industry. However, little is known about the effects of plasma technology on the biochemical characteristics of food, particularly nuts. Therefore, this study evaluated the potential adverse effects of cold plasma on the biochemical characteristics of pistachio in 5, 10, 20, and 40 min of treatment. The results indicated that compared to the control group, there were no significant changes in photosynthetic pigments, malondialdehyde, catalase, peroxide value, acidity value, moisture content, and sensory attributes of pistachio. However, a significant decrease in the linoleic acid (5 %) alongside an increase in the palmitic acid (8 %) for 40-minute plasma treatment was observed. The total carbohydrates and protein content of pistachios remained unchanged for the 10-minute plasma treatment, while prolonged treatment (20 and 40 min) significantly reduced these compounds compared to the control group, with protein levels decreasing by 12.29 % and 14.56 %, and carbohydrate levels decreasing by 22.03 % and 44.0 %, respectively. Therefore, plasma treatment time is a critical factor in nut processing. Subsequent research should improve device design and optimize treatment duration to regulate the risk and food safety concerns.